PENGARUH LATIHAN PEREGANGAN TERHADAP FLEKSIBILITAS LANSIA - Ibrahim, Renold C.; Polii, Hedison; Wungouw, Herlina (Universitas Sam Ratulangi, 2015)
Abstract: Flexibilityis the ability of a joint, muscles, and ligaments around it to move free lyandcomfortably in the space for the expected maximum. Flexibility is influenced by many factors. These factors are the muscles, tendons, ligaments, age, gender, body temperature and joint structure. Less flexibility may lead toa slower movement and injury pronetomuscles, ligaments, andothertissues. With increasing age, the person’s flexibility will reduce. The best way to increase the flexibility is stretching exercises. This study aimed to find the effect of stretching exercises for flexibility among the eldery. This was an experimental field study with pre-post test design. Samples were 30 elderly people who were in BPLU Senjah Cerah, Paniki Bawah. Samples were measured by using a goniometer flexibility before doing stretching exercises. After stretching exercises for 3 weeks, they were measured again with the goniometer. The results showed that stretching influenced the flexibility of the elderly (p<0.05), except the glexibility of the right arm flexion did not increase p =0.134(p>0.05). Conclusion: Stretching exercises can improve joint flexibility.Keywords: flexibility, stretching exercises, elderlyAbstrak: Fleksibilitas merupakan kemampuan dari sebuah sendi,otot dan ligamen di sekitarnya untuk bergerak dengan leluasa dan nyaman dalam ruang gerak maksimal yang diharapkan. Fleksibiltas dipengaruhi oleh banyak factor yaitu otot, tendon, ligamen, usia, jenis kelamin, suhu tubuh dan struktur sendi. Fleksibilitas yang kurang dapat menyebabkan gerakan lebih lamban dan rentan terhadap cedera otot, ligamen, dan jaringan lainnya. Dengan bertambahnya usia maka fleksibilitas seseorang akan berkurang. Cara terbaik meningkatkan fleksibilitas ialah dengan latihan peregangan. Penelitian ini bertujuan untuk melihat pengaruh latihan peregangan terhadap fleksibilitas. Penelitian ini bersifat eksperimental lapangan dengan rancangan pre-post test design. Sampel berjumlah 30 orang Lansia yang berada di BPLU Senjah Cerah, Paniki Bawah. Sampel di ukur fleksibilitasnya dengan menggunakan goniometer terlebih dahulu sebelum melakukan latihan peregangan Setelah latihan peregangan selama 3 minggu dilakukan pengukuran kembali dengan menggunakan goniometer. Hasil yang didapatkan terdapat pengaruh peregangan lingkup gerak sendi pada fleksibilitas lansia (p<0,05) kecuali pada fleksi lengan dextra tidak terjadi peningkatan fleksibilitas diperoleh nilai p = 0,134 (p>005). Simpulan: Latihan Peregangan dapat meningkatkan Fleksibilitas Sendi.Kata kunci: fleksibilitas, latihan peregangan, lansia